Chemical Composition of the Essential Oils of Matricaria recutita L. Belonging to Central and South Parts of Iran - M Ghanavati; SL Houshmand; H Zainali; F Abrahimpour (Institue of Medicinal Plants, ACECR, 2010)
Background: Chamomile )Matricaria recutita L. (is one of the important and ancient well-documented medicinal plants in the World. Origin of Chamomile plant species is determined in the Frontal Asia Gene Pool Centre, mainly Iran. Objective: The objectives of this research are to individuate the results of the Chemical Composition of the Chamomile Essential Oils that is originated from geographical various parts of center and south the Iranian country. Methods: In this research 9 chamomile flower samples belonging central parts and south of Iran (Tehran, Isfahan, Shiraz, Kerman belong central parts, Gachsaran, Baba Meydan, Noor Abad, Behbahan and Larestan belong south of Iran) collected during 2006 spring and analyzed qualitative-quantitative characteristics of Essential oil by GC/Ms method. Results: One population belonging to the South of Iran (The Zagros Mountains) was rich in α- Bisabolol (55-58%) but had low content of the essential oil. Samples from Baba Mydan and Noor abad were rich in α- Bisabololoxide (50-60%). Conclusion: This Chamomile biodiversity was created during long time process (evolution) in regard to evaluate the influence of eco-physiological conditions (biotic- and abiotic- factors) on the concrete place of chamomile population growth.